Highly Mutable Animal RNA Viruses: Adaptation and Evolution - Masako Nomaguchi; Akio Adachi (Frontiers Media SA, 2021)
Viruses are widely present in nature, and numerous viral species with a variety of unique characteristics have been identified so far. Even now, new emerging or re-emerging viruses are being found or re-found as novel viral classes or as quasi-species. Indeed, viruses are everywhere. Of note, viruses are pivotal as targets and tools of basic and applied sciences. On one hand, portions of the viruses are infectious for animals including humans, and cause various diseases in infected hosts by distinct mechanisms and at a different level of severity. While many of viruses are known to co-exist quietly with their hosts, pathogenic viruses certainly affect and threaten our society as well as individuals to provoke serious medical or economic attention. We should act against certain dreadful and highly infectious viruses as a global problem. Animal RNA viruses can readily mutate to adapt themselves in their hostile environments for their survival. Resultant viruses may sometimes show essentially altered phenotypes from the original parental strains. This fundamental and general property of animal RNA viruses represents major extensive issues of scientific, medical, and/or economic importance. In this Research Topic, we have focused on the high mutability of animal RNA viruses, and selected relevant articles on animal viruses of broad-ranges such as primate lentiviruses, influenza viruses, paramyxoviruses, flaviviruses, rabies virus, norovirus, picornaviruses, and picobirnavirus. Each article has taken up intriguing aspects of the subject viruses. We are sure that readers acquire important information on virus mutation, adaptation, diversification, and evolution, and hope that researchers in the field related to virology gain some solid hints from the reported articles for further virological and /or medical studies. Finally, we thank all the contributing researchers in this Research Topic, entitled “Highly Mutable Animal RNA Viruses: Adaptation and Evolution”, for their elegant and interesting works.